Manifesto for a post-carbon future. - Mason, Paul (New Statesman, 2019)
The author discusses the role of the political left and the problem of climate change. He mentions the time no longer available to decrease carbon emission, the role of capitalism in setting environmental policies,, and the lack of a complete response by the world's elite.